Respuesta :

Unless you made an error in the notation

Solve for b:
-4 a - 26 b = 0
Factor constant terms from the left hand side:
-2 (2 a + 13 b) = 0
Divide both sides by -2:
2 a + 13 b = 0
Subtract 2 a from both sides:
13 b = -2 a
Divide both sides by 13:
Answer: b = -(2 a)/13

Solve for a:
6 (a - b) - 5 (2 a + 4 b) = 0
Expand out terms of the left-hand side:
-4 a - 26 b = 0
Factor constant terms from the left hand side:
-2 (2 a + 13 b) = 0
Divide both sides by -2:
2 a + 13 b = 0
Subtract 13 b from both sides:
2 a = -13 b
Divide both sides by 2:
Answer:  a = -(13 b)/2